Acidification evidences of no-tilled soils of the central region of Argentina - Iturri, Laura Antonela (2011)
Empiric evidences indicate that agricultural soils of Argentina tend to acidification. The objective of this study was to determine pH values of, since several years, no-tilled and urea-fertilized-agricultural soils of Argentina. Results indicated that both, the actual pH (pHA) and the potential pH (pHP) values were lower in humid than in dry environments. The ratio between “mean annual precipitation:mean annual temperature” of the sites explained between 60 and 80% of pH values variability. This suggests that climatic conditions were responsible for current soil pH values. The pHA was 1.14 points higher tan pHP in all studied sites (p<<0.01), indicating that a generalized natural acidification process existed. In soils of drier environments, differences between both pHA and pHP were, on average, higher than 1.21, indicating that a more intense acidification. However, pH values were not low enough to affect the normal growth of crops and soil organisms. In soils of humid environments, differences between pHA and pHP were higher than 1.10, being pHA values (6.17 and 5.80) acid enough to affect the microbial activity and the development of pH sensitive crops. Fertilization with urea decreased pHA between 0.18 and 0.32 points in relation to non fertilized treatments (p<0.05), indicating that fertilization contributed to decrease pH values in the studied soils. It is concluded that fertilization with urea slightly increased the natural tendency to soil acidification in most of studied soils.